A study of the influence of substrate-binder relationship in tablet formulations by an analgesiometric method - Ahmed, Naeem Sarfraz 1937-
The macromolecules like starch, acacia, sodium carboxymethyl cellulose, cellulose acetate phthalate, polyvinyl pyrrolidone, polyethylene glycols, sodium alginate and cation-exchange resins are most frequently employed in preparation of medicinal tablets as binding agents, disintegrators, lubricants and coating materials (2). The object of this study was to determine the effect of binders on the activity of the substrate on a mole per mole relationship with respect to (a) onset of action, (b) duration of action, and (c) the intensity of action of the substrate. The binders used in this investigations were acacia and polyvinylpyrrolidone. The substrate chosen was phenylbutazone. The investigation consisted of construction of an analgesiometer, construction of a plastic catheter, screening and testing of the experimental animals, preparation of tablet triturates of placebo and combinations of various binders and the active ingredient and the comparison of the pharmacological parameters: onset, duration and intensity of action of the different experimental runs. It was observed that the pharmacological acitivity of phenylbutazone was greatly influenced by binders employed in tablet triturate formulations. The greater the mole ratio of binder with respect to substrate, the greater was the corresponding effect on the pharmacological parameters, namely, onset of action, duration of action and intensity of action. It was discovered that as the number of moles of binder was increased per number of moles of substrate, the onset of action was prolonged and the intensity of action was decreased.